The Content of Heavy Metal Elements Fe, Pb, Cu and Cr in Tukad Water, Badung, Dauh Puri Kauh Village With Atomic Absorption Spectrophotometry (AAS) Method - Mogi, Theresia Avila; Ratnawati, I Gusti Agung Ayu; Suardana, Putu (BULETIN FISIKA; Vol 24 No 2 (2023): BULETIN FISIKA August Edition, 2022)
Research has been carried out to test the content of heavy metal elements in Tukad Badung water, Dauh Puri Kauh Village using the Atomic Absorption Spectrophotometry (AAS) method. This study aims to determine the levels of heavy metals Fe, Pb, Cu, and Cr in Badung Tukad. The results of the analysis showed that Tukad Badung water contained heavy metals Fe, Pb, Cu and Cr of 0.4616 ± 0.2378 mg/L, 1.8068 ± 0.7051 mg/L, 2.3035 ± 2.883 mg/L, respectively and 1.9215 ± 0.0766 mg/L.